PELATIHAN KESEKRETARIATAN BAGI PENGURUS PIMPINAN DAERAH ‘AISYIYAH (PDA) KABUPATEN TAKALAR - Ratnawati; Mutmainna; Satriani Is, Sitti (LPPM Universitas Islam 45 Bekasi, 2024)
The Regional Executive of 'Aisyiah of Takalar district has recently carried out the inauguration and strengthening of the Muhammadiyah ideology to the new management of the PDA of Takalar district. This is the attraction of the candidate for the head of the Unismuh Makassar PkM Team who is also the deputy secretary of the PWA Culture, Arts and Sports Institute (LBSO) to conduct a secretarial training for all administrators or assemblies in the management of PDA Takalar district. Secretarial science is a very important part to be owned by every 'Aisyiyah organization administrator, both in the 'Aisyiyah Regional Executive (PWA), the 'Aisyiyah Regional Executive (PDA), the 'Aisyiyah Branch Executive (PCA), and the 'Aisyiyah Charity (AUA) in every region in South Sulawesi. The organizational apparatus of 'Aisyiyah, the Administration of the Secretariat of 'Aisyiyah, and the trial procedures at 'Aisyiyah are part of the science of secretarial. This is considered very important to know and be able to implement its knowledge in every implementation of the work program that has been agreed upon at the 2023 South Sulawesi PWA Regional Working Meeting (RAKERWIL) meeting organized by each assembly or institution